2002
DOI: 10.1161/01.str.0000029828.51413.82
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Early Serial C-Reactive Protein Measurements After First Ischemic Stroke

Abstract: Background and Purpose-Recent studies described an association between elevated levels of C-reactive protein (CRP) and outcome after ischemic stroke. We investigated the impact of early serial CRP measurements in hyperacute ischemic stroke on long-term outcome. Methods-One hundred twenty-seven consecutive patients without thrombolysis with a first ischemic stroke no more than 12 hours after symptom onset were examined. Serial CRP measurements were done at admission (CRP 1), within 24 hours (CRP 2), and withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
160
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 34 publications
17
160
2
Order By: Relevance
“…Serial serum PCT levels did not correlate with stroke mortality or neurologic outcome at discharge. Studies have correlated laboratory parameters with prognosis in acute stroke, sometimes with conflicting results [5][6][7]. Prognostic utility of laboratory parameters in acute stroke is limited by the need to perform serial measurements, together with the interrelation of at least some of the inflammatory markers.…”
Section: To the Editormentioning
confidence: 99%
“…Serial serum PCT levels did not correlate with stroke mortality or neurologic outcome at discharge. Studies have correlated laboratory parameters with prognosis in acute stroke, sometimes with conflicting results [5][6][7]. Prognostic utility of laboratory parameters in acute stroke is limited by the need to perform serial measurements, together with the interrelation of at least some of the inflammatory markers.…”
Section: To the Editormentioning
confidence: 99%
“…The association of both high levels of hs-CRP and ischemic heart disease with this infarct pattern may reflect the unstable plaque burden in these patients. An increased prevalence of high CRP levels in patients with ischemic stroke and ischemic heart disease was reported previously [22,24]. In addition, it is generally accepted that inflammation is important in plaque rupture, including an association between elevated CRP levels and an increased risk of ischemic events or high-risk unstable plaque morphology [25,26].…”
Section: Discussionmentioning
confidence: 92%
“…Data from other studies also suggest this. hs-CRP levels measured during the acute stage (during admission or several days after onset of symptoms) of ischemic heart disease or stroke/TIA predict the risk of recurrent events and prognosis [22,16,[33][34][35]. Further studies with serial hs-CRP measurement are needed; it was reported that an increase of hs-CRP within 3 h after stroke compared with the prestroke value [21], and hs-CRP concentrations increased with time after onset of stroke [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations